A185 THE IMPACT OF PRIOR SURGERY ON ADVERSE PREGNANCY OUTCOMES IN PREGNANT PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (4th March 2021) - Chis, R; Tandon, P; Huang, V W
Abstract: Background: During the course of inflammatory bowel disease (IBD), approximately 20% of patients with ulcerative colitis (UC) and 80% of Crohn's disease (CD) patients will require surgery. The most common operation is total proctocolectomy and ileoanal pouch anastomosis (IPAA) for UC patients and ileocecal (IC) resection for CD. In pregnant IBD patients, guidelines name the presence of IPAA as a relative indication for Cesarean section (C-section). The effect of prior IBD-related surgery on mode of delivery and pregnancy-related outcomes remains unknown. Aims: To describe pregnancy-related outcomes in pregnant women with IBD who have undergone prior IBD-related surgery. Methods: We performed a retrospective cohort study of pregnant women with IBD including those with prior IBD-related surgeries including IPAA, IC resection, total or partial colectomy and ileostomy formation who delivered an infant at our medical center from 2016 to 2020. We assessed the mode of delivery, delivery characteristics (emergency vs. planned C-section) and maternal and neonatal outcomes Results: Fifty-six UC patients and 64 CD patients were included in the analysis, of which 10 and 24 had undergone prior IBD-related surgery, respectively. The mean age at conception was 34.10 years in the surgical UC group and 30.30 years in the surgical CD group. Mode of delivery : C-section rates were higher in post-surgical compared to non-surgical UC patients (70% vs. 30.4%, p = 0.02). Similar numbers of C-sections were performed emergently in the surgical compared to non-surgical UC group (10% vs. 18%, p = 0.53). Comparatively, there was no significant difference in C-section rates in post -surgical compared to non-surgical CD mothers (50% vs. 40%, p = 0.44), with 13% performed emergently in both groups. Maternal outcomes: Gestational diabetes developed in 10% of surgical UC and 4.5% of surgical CD patients. Premature rupture of membranes developed in 10% of surgical UC and 9.1% of surgical CD patients. There was no difference in pre-eclampsia rates in the surgical and non-surgical CD groups (9.1% vs 13.2%, p = 0.64). Neonatal outcomes : There was no significant difference in pre-term birth rates in post-surgical compared to non-surgical UC mothers (10% vs. 15.2%, p = 0.67) or in surgical compared to non-surgical CD mothers (13.6% vs. 5.1%, p = 0.29). Neonatal Intensive Care Unit (NICU) requirements were higher in infants born to post-surgical CD compared to non-surgical CD mothers (18.2% vs. 2.7%, p = 0.04). More low birth weight (LBW) infants were born to post-surgical CD vs non-surgical CD mothers (13.6% vs. 0%, p = 0.02). Conclusions: Women with IBD who have had prior IBD-related surgery may be at increased risk of developing adverse gestational and neonatal outcomes. Women with surgical UC have an increased incidence of Cesarean delivery. Funding Agencies: None